Converting of nuisance cyanobacterial biomass to feedstock for bioethanol production by regulation of intracellular carbon flow: Killing two birds with one stone. (October 2021) - Huang, Yingying; Chen, Xuechu; Liu, Silu; Lu, Jinzhong; Shen, Yingshi; Li, Lei; Peng, Lin; Hong, Jingjie; Zhang, Qiuzhuo; Ostrovsky, Ilia
Abstract: Outbreaks of cyanobacterial harmful algal blooms present a serious threat to ecosystem safety and human well-being. Removal of toxic cyanobacterial biomass from freshwaters and its safe utilization is a worldwide problem. We showed that regulation of intracellular carbon flow by applying nitrogen deprivation strategy with light and inorganic carbon manipulation during the cultivation of cyanobacterium Microcystis allows efficiently convert its biomass into the biofuel feedstock. The proteomic analysis demonstrated that highly efficient feedstock production can be achieved during Microcystis culturing by nitrogen deprivation, which slows down the catabolic consumption of carbohydrates in cells. Further, we developed a novel approach that allows converting the natural Microcystis biomass into carbohydrate-rich feedstock by maintaining a high rate of carbohydrate production at minimal biomass losses. The yield attains 0.22 g ethanol per gram dry biomass, which is in the range of the ethanol yield of sugarcane, but higher than the values of sugarcane waste. The suggested approach provides cost-effective technology for sustainable green energy production from nuisance cyanobacterial biomass. The massive removal of toxic cyanobacterial biomass for bioethanol productions can mitigate the harmful cyanobacterial blooms in eutrophic lakes, and positively affect their restoration. Highlights: N-deprivation enhances carbohydrate content in Microcystis cells to 2.7 fold. Natural Microcystis scum can be manipulated to produce carbohydrate-rich feedstock. Slowing down in catabolic consumption induces carbohydrate accumulation. The bioethanol yield from carbohydrate-rich Microcystis attains 0.22 g -1 dry biomass. This study sheds light on mitigation of CyanoHABs by converting into green energy.